A study of the maintenance of patents by the non-residents in India: insights for strategic management of patents. (2015) - Krishna, Vinita; Jain, Sudhir K.
Managing patents is a core issue in the intellectual property management (IPM) of the firms. It entails two important activities: the patenting of new innovations and the renewal of patents. With the research on renewal data gaining momentum, this paper tries to study the renewal of patents in the pharma sector in India. Adopting a unique approach of studying both active and ceased patents of non-resident applicants in India, with the aid of descriptive methods and statistical tools as SPSS following trends, has been found. Business firms are the dominant patentees and single inventorship an emerging trend in India. While renewal patterns are quite applicant category specific, grant period is independent of the applicant category. In case of the patents category (ceased or active), maintenance duration is independent of the number of inventors but effective life of the patents varies with category of patents. The higher propensity to patent and maintenance show linkage with specific technology fields and the portfolio size.